2004
DOI: 10.1177/154405910408300407
|View full text |Cite
|
Sign up to set email alerts
|

Somatosensory-evoked Fields for Gingiva, Lip, and Tongue

Abstract: To localize the oral primary somatosensory cortex, we measured somatosensory-evoked fields for the lip, gingiva, and tongue in six healthy subjects. The latency of the first peak of the posterior-oriented current in the contralateral hemisphere was 50.9 +/- 8.3 ms for the gingiva, significantly shorter than those for the lip and tongue peaks. The equivalent current dipole was localized on the central sulcus. The gingival dipole was localized significantly inferior to the lip dipole but not different from the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
45
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 53 publications
(49 citation statements)
references
References 27 publications
4
45
0
Order By: Relevance
“…The present study found that the lip ECD was located higher than the tongue ECD of the SEFs, corresponding to the previous findings by cortical stimulation (Penfield and Boldrey 1937;Penfield and Rasmussen 1950), cortical recording of somatosensory potentials (McCarthy et al 1993), and SEFs (Yamashita et al 1999;Nakahara et al 2004). However, we found no statistical difference between the ECDs of the buccal gingiva, lingual gingiva, and tongue, in contrast to the previous conclusion by Penfield and colleagues (Penfield and Rasmussen 1950) that gingival SI is located higher than tongue SI, but which was based on complicated results.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…The present study found that the lip ECD was located higher than the tongue ECD of the SEFs, corresponding to the previous findings by cortical stimulation (Penfield and Boldrey 1937;Penfield and Rasmussen 1950), cortical recording of somatosensory potentials (McCarthy et al 1993), and SEFs (Yamashita et al 1999;Nakahara et al 2004). However, we found no statistical difference between the ECDs of the buccal gingiva, lingual gingiva, and tongue, in contrast to the previous conclusion by Penfield and colleagues (Penfield and Rasmussen 1950) that gingival SI is located higher than tongue SI, but which was based on complicated results.…”
Section: Discussionsupporting
confidence: 92%
“…However, only the lingual side of the gingiva was stimulated in our previous study, so the location of the SI cortices of the buccal and lingual gingiva areas might be different. The present study extended our previous investigation (Nakahara et al 2004) by adding stimulation points including the buccal side of the gingiva to delineate the fine SI somatotopy of the gingiva area.…”
Section: © 2005 Tohoku University Medical Presssupporting
confidence: 54%
See 3 more Smart Citations